Harmonization of Fines (Taʿzir), Compensation (Ta’wiḍh) and the Financial Information Service System (SLIK) in Sharia Financial Institutions as Cumulative Sanctions for Defaulting Debtors: Analysis of DSN-MUI Fatwa and POJK - Nur Irmandi; Abdal; Syamsurijal; Ratna Istianah (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study analyzes penalties (ta’zir) and compensation (ta’wiḍh) in Islamic financial institutions, as well as the role of the Financial Information Service System (SLIK) as a form of cumulative sanctions for defaulting debtors. This study focuses on a crucial research gap: the lack of a harmonized framework between sharia sanctions (DSN-MUI) and reputation sanctions (OJK), which has the potential to cause injustice due to cumulative sanctions for debtors. Focusing on DSN-MUI Fatwas No. 17/2000, No. 43/2004, No. 129/2019, and OJK Regulation No. 18/POJK.03/2017, this study uses a normative juridical method. This study finds that the DSN-MUI fatwas affirm the principle of proportionality by limiting ta’wiḍh to real costs and establishing ta’zir as a disciplinary instrument. However, their implementation in the field shows variation. Integration with reputation sanctions through SLIK, while strengthening oversight, creates a dual sanctions regime that raises issues of fairness. As an original contribution, this article proposes a “tiered sanction model” as a new solution for harmonization. This study concludes that the current dualistic system, without harmonization, systematically disadvantages debtors and requires an immediate regulatory review.